Biographies of Abraham and Other Men - Millard, Alan (HIPHIL Novum, 2024)
The biography of Abraham can be compared with other biographies from the second millennium BC which are often treated as fictional. The motifs in the lives of the Egyptian Sinuhe and the Syrian Idrimi are typical. Does the recurrence of such motifs indicate they are imaginary or may they be based on the lives of real characters? Reasons for believing Sinuhe and Idrimi were historical, not legendary, figures are advanced as analogies for accepting that the biblical narratives of Abraham also tell of events in the life of an historical person.